The Effects of Immediate vs Gradual Reduction in Nicotine Content of Cigarettes on Smoking Behavior: An Ecological Momentary Assessment Study - Li, Qianling; Chen, Xijing; Li, Xiuli; Gorowska, Monika; Li, Zimin; Li, Yonghui (Frontiers in Psychiatry, 2022)
Background In recent years, much research has examined the effects of various interventions and treatments for smoking cessation. The results suggest that interventions targeting changes of nicotine content can help smokers reduce tobacco use or quit smoking. A number of clinical studies show that smokers who received an immediate reduction in nicotine content to very low levels have significantly greater reductions in the number of cigarettes smoked and toxic substance exposure compared to those with gradual reductions. However, from the perspective of smoking craving, whether the immediate and gradual reduction in nicotine content reduce smoking by reducing cravings needs further investigation. Methods 74 eligible Participants were randomly allocated to one of the two experimental conditions: (1) immediate reduction to 0.1 mg of nicotine per cigarette (n = 40); (2) gradual reduction from 1.0 (0.8 g ~ 1.2 mg) to 0.1 mg of nicotine per cigarette (n = 34). All participants completed 1-week baseline period during which they smoked their usual cigarette, followed by 16-week of interventions. The primary outcomes included cigarette cravings and number of cigarettes smoked per day (CPD); secondary outcomes included the number of cigarette-free day and emotional states. Results Among the 52 participants [51 (98.1%) men; mean (SD) age, 33.44 (6.71) years; mean (SD) CPD, 16.83 (9.94)] who completed the trial, significantly lower cravings for cigarettes were observed in the immediate (n = 25) vs. gradual nicotine reduction group (n = 27) in the morning (t = −2.072, p = 0.039) and after dinner (t = –2.056, p = 0.041). Compared with the baseline daily smoking, the number of cigarettes smoked per day was significantly reduced at the beginning of week 12 in the immediate nicotine reduction group (p = 0.001) and at week 16 in the gradual nicotine reduction group (p < 0.001). The number of participants with any cigarette-free day was not significantly different between the groups (p = 0.198). The number of cigarette-free days was significantly more in the immediate vs. gradual nicotine reduction group (p = 0.027). Conclusions The significantly lower cravings were observed in the immediate vs. gradual nicotine reduction group, and led to faster reduction in the number of CPD, and a significant increase in the number of cigarette-free days. These findings add to the evidence base for reduced nicotine content in cigarettes. Clinical Trial Registration ClinicalTrials.gov, identifier: ChiCTR2100048216.